An Informational interpretation of the Aveyron’s Wild Child: L’enfant sauvage (1970) - Hans CONTRERAS PULACHE; Alexa Ivonne JOYA QUISPE; Dafne Solange MOYA MALDONADO; Angello Jesús OSCANOA CHÁVEZ; Yumi Shannon PÉREZ LY; Jeel MOYA SALAZAR (Revista de Medicina y Cine / Journal of Medicine and Movies, 2019)
On the basis of the film: L'enfant Sauvage (1970) by François Truffaut, we proposed to discuss the following concepts: humanization and socialization, from the perspective of the Sociobiological Information Theory. And then, we made an interpretation of the changes that occur in the nervous system of a wild (feral) child at the (belated) inception of its socialization. In summary, we seek to answer the following questions: I. what is Itard looking for in Víctor: humanize it or socialize it? And, II. How can the changes that happen to Victor after his encounter with Itard be interpreted neurologically?